Sincronicidade: dados e perspectivas - Ricelli, Izete de Oliveira (2010)
This theoretical study sought to identify the possible development of the concept of synchronicity proposed by C. G. Jung, since its publication in 1952 until the present moment. The nature of this research is bibliographical and a literature review of original essays on Jung by classic and contemporary Jungian authors was performed, dealing with the concept in the theoretical point of view. The physics of the thermodynamic processes developed from the last decades of the twentieth century sets up a paradigm shift in science that is designated as post-modern or as a paradigm of complexity. Therefore, it is suggested that the so-called Complexity Theory can be applied as an epistemological and theoretical background to the concept of synchronicity. This proposal conceives the phenomena as synchronistic moments of critical self-organization that can be found in nature in general and are characteristic of periods of transition. Transition phases are characterized, in the human sphere, by the emergency of meaning provided by synchronicities and reorganize the system of symbolism and psychophysical as a whole. Thus, considerations are presented to help understanding the concepts